2010
DOI: 10.1212/wnl.0b013e3181ea9ee3
|View full text |Cite
|
Sign up to set email alerts
|

Nongenetic factors influence severity of episodic ataxia type 1 in monozygotic twins

Abstract: Objective: Episodic ataxia type 1 (EA1) is a monogenic channelopathy caused by mutations of the potassium channel gene KCNA1. Affected individuals carrying the same mutation can exhibit considerable variability in the severity of ataxia, neuromyotonia, and other associated features. We investigated the phenotypic heterogeneity of EA1 in 2 sets of identical twins to determine the contribution of environmental factors to disease severity. One of the mutations was also found in a distantly related family, providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 7 publications
1
38
0
Order By: Relevance
“…However, the specific functional consequences of mutations do not fully correlate with the clinical phenotype of patients, but instead show phenotypic variability. Thus, mutations in KCNA1 have been identified in a wide phenotypic spectrum, which includes large differences in severity and frequency in EA1 attacks, epilepsy with myokymia, isolated neuromyotonia, persistent cerebellar dysfunction with cognitive delay, and hypomagnesemia among others . Here we report the clinical, genetic, and functional study of KCNA1 /Kv1.1 in a family with EA1 and identify the novel mutation p.Arg324Thr that results in reduced potassium currents and changes in the voltage‐dependence of activation and inactivation.…”
mentioning
confidence: 88%
“…However, the specific functional consequences of mutations do not fully correlate with the clinical phenotype of patients, but instead show phenotypic variability. Thus, mutations in KCNA1 have been identified in a wide phenotypic spectrum, which includes large differences in severity and frequency in EA1 attacks, epilepsy with myokymia, isolated neuromyotonia, persistent cerebellar dysfunction with cognitive delay, and hypomagnesemia among others . Here we report the clinical, genetic, and functional study of KCNA1 /Kv1.1 in a family with EA1 and identify the novel mutation p.Arg324Thr that results in reduced potassium currents and changes in the voltage‐dependence of activation and inactivation.…”
mentioning
confidence: 88%
“…Owing to a noticeable interfamilial and intrafamilial phenotypic variability, genotypeϪphenotype correlation has been extremely difficult to establish reliably (22). Differences in severity and frequency of EA1 attacks have been reported even in identical twins (13).…”
mentioning
confidence: 99%
“…These results indicated that the degree of impairment of the delayed rectifier function of affected neurons is related to the type and number of mutated subunits that make up the tetrameric Kv1.1 channels (D'Adamo et al, 1998). Coexpression experiments also showed that some mutant subunits exert dominant negative effects on WT subunits, resulting in less than half the normal current, whereas others have virtually no effect (Zerr et al, 1998;D'Adamo et al, 1999;Rea et al, 2002;Imbrici et al, 2006Imbrici et al, , 2011Graves et al, 2010). Kv1.1, Kv1.2, and Kv1.4 are the most abundant subunits expressed in the central nervous system and are assembled to form heteromeric channels composed of Kv1.1/Kv1.2 and Kv1.1/Kv1.4 subunits.…”
Section: Ea1: Genetics and Molecular Pathogenesismentioning
confidence: 93%
“…To date KCNA1 is the only gene known to be associated with EA1, and more than 20 KCNA1 mutations have been identified by sequence analysis, which are distributed throughout the gene (for a review see D'Adamo et al, 2012). Symptom heterogeneity among individuals harboring the same mutation may reflect the interplay of nongenetic factors (Graves et al, 2010). Indeed, even identical twins harboring the same EA1 mutation displayed unexpectedly large differences in the severity and frequency of attacks (Graves et al, 2010).…”
Section: Ea1: Genetics and Molecular Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation